Effect of therapeutic hypothermia on myocardial dysfunction in term neonates with perinatal asphyxia – a randomized controlled trial. (17th September 2018) - Rakesh, K.; Vishnu Bhat, B.; Adhisivam, B.; Ajith, P.
Abstract: Objective: To evaluate the effect of therapeutic hypothermia on myocardial dysfunction in term neonates with perinatal asphyxia. Material and methods: This randomized controlled trial (RCT) conducted in a tertiary care teaching hospital, south India included 120 newborns with perinatal asphyxia that were randomized to two groups (therapeutic hypothermia and normothermia). Cardiac enzyme profile changes between groups were assessed at 0, 24, 72 h CPK-MB and troponin I levels were estimated by immune inhibition and quantitative immunochromatography methods, respectively. Electrocardiography (ECG) and Echocardiography (ECHO) were done at 0 and 72 h to evaluate the cardiac function and pulmonary hypertension. Neurodevelopment was assessed at 6 months of age in both groups using Developmental Assessment Scales for Indian Infants. Results: The median values of CPK-MB in the normothermia and hypothermia groups at 0, 24, and 72 h were 198, 127, and 92 IU/L and 202, 111 and 64 IU/L, respectively. The median values of troponin I in normothermia and hypothermia groups at 0, 24, and 72 hrs were 2.45, 1.53, and 0.9 ng/mL and 1.97, 0.93, and 0.01 ng/mL, respectively. ECG and ECHO findings also suggest lesser myocardial dysfunction in therapeutic hypothermia group compared with the normothermia group. Conclusions: Therapeutic hypothermia significantly decreases the myocardial damage in term asphyxiated neonates.